Attitude to Foreign Languages in Russian Literature - Graf, Alexander (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2019)
The article traces the dynamics of use and the role of foreign languages in the Russian literature in the 18th-20th centuries. The main subject of discussion are the factors regulating the attitudes towards foreign languages, ranging from individual to cultural-historical ones. Attention is focused on the changes in the vector of cultural orientation understood as a set of heterogeneous phenomena.